CARBON ISOTOPE STRATIGRAPHY AND THE PROBLEM OF A PRE-TOMMOTIAN STAGE IN SIBERIA - Kouchinsky A.; Bengtson S.; Missarzhevsky V.V.; Pelechaty S.; Torssander P.; Val'kov A.K. (My University, 2001)
Carbon isotopic oscillations are useful to elucidate the stratigraphy and biogeochemical events around the Precambrian-Cambrian transitional beds across the Siberian Platform. The similarity of trends and amplitudes of the carbon isotopic curves, together with biostratigraphic and sequence-stratigraphic markers from the Anabar Uplift, provide a precise correlation with the southern part of the Siberian Platform. Diagenesis of argillaceous limestones of the Emyaksin Formation has apparently not affected the primary isotopic variations. The resulting curve is nearly identical in sections about 100 km apart in the Tommotian–Atdabanian portion of the formation. Relatively frequent and pronounced isotopic oscillations in the lower beds of the Emyaksin Formation fit between features I and II of the southern Siberian isotopic reference scale but are undetected therein owing to the depositional hiatus at the base of the Tommotian Stage in its type section. This confirms the transgressive onlap from the north suggested by previous studies, and makes the appearance of the Cambrian skeletal fossils on the Siberian Platform less abrupt. The hiatus in the south appears to embrace at least two biostratigraphic zones as recognized in the north. The case is strengthened for a pre-Tommotian Cambrian Stage in Siberia, the biostratigraphic framework for which has been elaborated earlier.
Keywords: Manykaj and Emyaksin formations; Anabar Uplift; Siberian Platform; Neoproterozoic–Cambrian transitional beds; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская